2022
DOI: 10.1111/jfpp.16699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic pretreatment on flavor characteristics of brewer's yeast‐peanut meal hydrolysate/xylose Maillard reaction products

Abstract: In this study, we investigated the effect of ultrasonic pretreatment on the flavor characteristics of Maillard reaction products (MRPs) because ultrasound enhances the Maillard reaction (MR). Brewer's yeast‐peanut meal hydrolysate was subjected to an ultrasonic treatment, followed by a thermal treatment to induce the MR. Then, several properties of the MRPs were investigated. Compared to the untreated samples, the ultrasound‐treated samples presented looser microstructures, which were conducive to the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…US pretreatment at 100 W, 20 min, and 30 • C provided enough energy to change the protein secondary structure and favored the production of peptides/amino acids that accelerated the Maillard reaction. In another study, it was indicated that the formation of Maillard conjugates between the brewer's yeast-peanut meal hydrolysate and glucose was affected by the US power, and conjugates with improved functional and sensorial properties were obtained when the US pretreatment was performed at 200 W [29]. Above this limit, the formation of Maillard products decreased and flavor characteristics were inferior because sonication inhibited the polymerization of intermediates and consequently the conversion to melanoidins.…”
Section: Ultrasound (Us)mentioning
confidence: 99%
“…US pretreatment at 100 W, 20 min, and 30 • C provided enough energy to change the protein secondary structure and favored the production of peptides/amino acids that accelerated the Maillard reaction. In another study, it was indicated that the formation of Maillard conjugates between the brewer's yeast-peanut meal hydrolysate and glucose was affected by the US power, and conjugates with improved functional and sensorial properties were obtained when the US pretreatment was performed at 200 W [29]. Above this limit, the formation of Maillard products decreased and flavor characteristics were inferior because sonication inhibited the polymerization of intermediates and consequently the conversion to melanoidins.…”
Section: Ultrasound (Us)mentioning
confidence: 99%